PROGRAM MODIFICATION ON THE NODEMCU USING THE OVER THE AIR METHOD THE CASE OF AIR MONITORING EQUIPMENT - Andriany, Oktaviani Laurensia; Marpaung, Jannus; Tjahjamooniarsih, Neilcy (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Internet of Things (IoT) is a technology that allows devices to connect to other devices via the Internet network. Over The Air (OTA) is a wireless delivery mechanism for transmitting data and performing updates. Modify the NodeMCU by updating it so that the sensor condition is active by uploading files containing programs wirelessly successfully carried out by the method Over The Air. Mark Packet loss 0% at the time upload file from laptop to NodeMCU when activating 1 DHT22 sensor and 2 DHT22 sensors and MQ7 can only reach a distance of 40 m in use Wi-Fi with a working frequency of 2.4 GHz. The difference in value Delay between updating just 1 sensor, namely DHT22, and 2 sensors, namely DHT22 and MQ7, at a distance of 5 m it is 0.1 ms, at a distance of 10 m it is 0.4 ms, at a distance of 20 m and 30 m it is 0.5 ms, and at a distance 40 m is 0.7 ms. Meanwhile, at a distance of 50 m - 100 m, updates using the over-the-air method can no longer be updated because the ESP8266 NodeMCU can no longer connect to the network Wi-Fi with a frequency of 2.4 GHz.